DRIVER: Building a Sustainable Infrastructure of European Scientific Repositories - Lossau, Norbert; Peters, Dale (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
DRIVER has a clear vision: All research institutions in Europe and worldwide make all their research publications openly accessible through institutional repositories. The vision follows the Berlin Declaration, which called in October 2003 for ‘free and unrestricted access to sciences and human knowledge representation worldwide’. Initiated by the internationally renowned German research organisation the Max-Planck-Society, and signed by many international research organisations and institutes, the Berlin Declaration has set a political statement. In building a sustainable infrastructure for scientific repositories, DRIVER brings to this statement the reality of scholarly communication in the future.